2002
DOI: 10.1046/j.1469-8137.2002.00364.x
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizas influence plant diversity and community structure in a semiarid herbland

Abstract: Summary• The contribution of arbuscular mycorrhizas (AM) to plant community structure and diversity is reported here in an annual herbland in southern Australia.• Mycorrhizal colonization was reduced in field plots by applying the fungicide benomyl as a soil drench. The mycorrhiza-responsiveness of plant species was assessed in intact soil cores containing the indigenous AM fungi and in a pot experiment using an isolate of Glomus mosseae .• Glasshouse experiments showed that Medicago minima, Vittadinia gracili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
159
2
10

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 216 publications
(182 citation statements)
references
References 42 publications
11
159
2
10
Order By: Relevance
“…By the end of this study, plots had received either two or three years of benomyl application. Benomyl is effective in reducing colonization of arbuscular-mycorrhizal fungi (AMF) Nichols 1988, Smith et al 2000) and has been widely used in ecological studies (e.g., Newsham et al 1994, 2002, O'Connor et al 2002, Callaway et al 2003. However, benomyl also causes a variety of unintended effects, including suppression of parasitic fungi (Newsham et al 1994) and nematodes (Schmidt et al 2000).…”
Section: Mycorrhizal Suppressionmentioning
confidence: 99%
“…By the end of this study, plots had received either two or three years of benomyl application. Benomyl is effective in reducing colonization of arbuscular-mycorrhizal fungi (AMF) Nichols 1988, Smith et al 2000) and has been widely used in ecological studies (e.g., Newsham et al 1994, 2002, O'Connor et al 2002, Callaway et al 2003. However, benomyl also causes a variety of unintended effects, including suppression of parasitic fungi (Newsham et al 1994) and nematodes (Schmidt et al 2000).…”
Section: Mycorrhizal Suppressionmentioning
confidence: 99%
“…Tem-se chamado atenção para a capacidade desses micossimbiontes em influenciar as relações interespecíficas das espécies vegetais na comunidade, como a competição por nutrientes, quando estes são escassos, com consequente alteração na diversidade e na estrutura de comunidades de plantas (O'CONNOR et al, 2002).…”
Section: Introductionunclassified
“…Recently, it has also been demonstrated that arbuscular mycorrhizal (AM) associations can protect host plants under As contamination, even for the As-tolerant plant species, such as Chinese brake fern (Pteris vittata L.) (Liu et al, 2005;Chen et al, 2007b). Moreover, it is well known that AM symbioses have major influences on plant coexistence and plant community diversity (Zobel et al, 1997;O'Connor et al, 2002). Plants associated with AM fungi can successfully colonize sites contaminated by heavy metals, such as mine tailings that normally can hardly support any plant growth (Khan et al, 2000;Pennisi, 2004).…”
Section: Introductionmentioning
confidence: 99%